2010
DOI: 10.1002/jhm.808
|View full text |Cite
|
Sign up to set email alerts
|

Gaining efficiency and satisfaction in the handoff process

Abstract: BACKGROUND:Handoffs, or transfers of patient care responsibility, occur frequently on hospitalist teams. The reliability and efficiency of the handoff process is a national and local concern. Most studies in the literature regard physicians‐in‐training. We studied the morning handoff process of hospitalist teams comprised of staff physicians and nurse practitioner and/or physician assistants.METHODS:An improvement team observed morning handoffs. Four problems were identified: unpredictable start and finish tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…This same ability, taking pieces of data and applying it to the clinical problem, is also essential to clinical summarization. The students' perception that preparation and review enhanced the handoff experience is also supported in the clinical realm wherein there is evidence that reviewing material prior to receiving a handoff improves the quality of the handoff (Burton et al, ). Together, this suggests that although the students may not recognize the connection, the impact of the anatomic SBAR on students' learning strategies may also help improve their handoff skills within the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…This same ability, taking pieces of data and applying it to the clinical problem, is also essential to clinical summarization. The students' perception that preparation and review enhanced the handoff experience is also supported in the clinical realm wherein there is evidence that reviewing material prior to receiving a handoff improves the quality of the handoff (Burton et al, ). Together, this suggests that although the students may not recognize the connection, the impact of the anatomic SBAR on students' learning strategies may also help improve their handoff skills within the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Most recently, researchers have begun to study the impact of year-end handoffs on patient safety in resident ambulatory care practices. Young et al, 7 in a multifaceted intervention in a psychiatric outpatient practice, demonstrated that the categorical designation of patients as 'acute' or 'not acute' by outgoing clinicians effectively identified patients at higher risk for hospitalization during transitions.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of strategies have been utilized to standardize handoffs. Examples include the use of mnemonics, electronic resources, preformatted handoff sheets, and optimization of the handoff environment . The primary outcomes for many of these studies center on the provider by measuring their retention of patient facts and completion of tasks after handoff, for example.…”
mentioning
confidence: 99%
“…Providers in our division work on 3 shifts: day, evening, and night. In 2009, we developed a face‐to‐face morning handoff, during which night‐shift providers hand off patient care to day‐shift providers incorporating an electronically generated service information list . Given that the evening shift ends well before the day shift begins, the evening‐shift providers do not participate in this face‐to‐face handoff of care for patients they admit to day providers.…”
mentioning
confidence: 99%